Pembelajaran Fikih Berbasis Audio-Visual Sebagai Media Dalam Meningkatkan Prestasi Belajar Siswa Di MA Nurul Yaqin Situbondo - Eka Diana; Jannatun Firdaus (Universitas Yudharta Pasuruan, 2021)
This study aims to analyze the use of audio-visual media in improving student learning achievement in fiqh learning at MA Nurul Yaqin Situbondo. The form of this research is classroom action research using the Kut Lewin model. The study was conducted in two cycles with four steps in one cycle, namely planning, acting, observing, and reflecting. Data collection techniques using observation, in-depth interviews, performance appraisal and documentation. The data were analyzed by using qualitative and quantitative descriptive techniques. The results showed that there was an increase in the learning achievement of students in fiqh learning using the audio-visual method. The value of the success of students in cycle I and cycle II classically with a percentage of completeness in the pre-cycle (before) audio-visual learning was carried out by 48%, in cycle I the implementation of audio-visual learning the percentage of student completeness increased to 72% and there needs to be an increase with implementation cycle II because it is still less 80%. In the second cycle the implementation of audio visual learning increased the percentage of students' completeness to 88% which was in the very good classification.